Attenuated psychotic symptom interventions in youth at risk of psychosis: A systematic review and meta‐analysis. Issue 1 (11th May 2018) - Devoe, Daniel J.; Farris, Megan S.; Townes, Parker; Addington, Jean
Abstract : Aim: Attenuated psychotic symptoms (APSs) have been the primary emphasis in youth at clinical high risk (CHR) for psychosis for assessing symptomology and determining subsequent transition to a psychotic disorder. Previous reviews primarily focused on the efficacy of cognitive behavioural therapy (CBT) on APS; however, a comprehensive assessment of other interventions to date is lacking. Therefore, we conducted a systematic review and meta‐analysis of all intervention studies examining APS in CHR youth. Method: The authors searched Embase, CINAHL, PsycINFO, Medline and EBM from inception to May 2017. Studies were selected if they included any intervention that reported follow‐up APS in youth at CHR. Interventions were evaluated and stratified by time using both pairwise and network meta‐analyses (NMAs). Due to the differences in APS scales, effect sizes were calculated as Hedges g and reported as the standardized mean difference (SMD). Results: Forty‐one studies met our inclusion criteria. In pairwise meta‐analyses, CBT was associated with a trend towards reduction in APS compared to controls at 12‐months. In the NMA, integrated psychological therapy, CBT, supportive therapy, family therapy, needs‐based interventions, omega‐3, risperidone plus CBT and olanzapine were not significantly more effective at reducing APS at 6 and 12 months relative to any other intervention. Conclusions: CBT demonstrated a slight trend at reducing APS at long‐term follow‐up compared to controls. No interventions were significantly more effective at reducing APS compared to all other interventions in the NMA. [Correction added on 4 June 2018, after first online publication: Some parts of the Abstract section particularly 'Results' and 'Conclusions' have been corrected.]